2000
DOI: 10.2337/diabetes.49.7.1169
|View full text |Cite
|
Sign up to set email alerts
|

Decreased insulin responsiveness of glucose uptake in cultured human skeletal muscle cells from insulin-resistant nondiabetic relatives of type 2 diabetic families.

Abstract: To investigate the contribution of inherited biochemical defects to the peripheral insulin resistance of type 2 diabetes, we studied cultured skeletal muscle from 10 insulin-resistant nondiabetic first-degree relatives of type 2 diabetic families and 6 control subjects. Insulin stimulation of glucose uptake and glycogen synthesis was maximal in myoblasts. Insulin-stimulated glucose uptake (fold-stimulation over basal uptake) was decreased in relative compared with control myoblasts at 0.001 µmol/l (0.93 ± 0.05… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
48
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 69 publications
(76 reference statements)
6
48
0
Order By: Relevance
“…As indicated previously [28], cells established from Type 2 diabetic patients had the same rate of myoblast growth and fusion into myotubes as cells from control subjects. In agreement with other studies [21,23,24,25], there was no apparent morphological difference between differentiated muscle cells from non-diabetic and diabetic subjects.…”
Section: Methodssupporting
confidence: 81%
See 1 more Smart Citation
“…As indicated previously [28], cells established from Type 2 diabetic patients had the same rate of myoblast growth and fusion into myotubes as cells from control subjects. In agreement with other studies [21,23,24,25], there was no apparent morphological difference between differentiated muscle cells from non-diabetic and diabetic subjects.…”
Section: Methodssupporting
confidence: 81%
“…Primary cultures of human muscle cells display numerous features of mature skeletal muscle [21,22]. More importantly, myotubes established from Type 2 diabetic patients conserve the diabetic phenotype, including decreased insulin responsiveness of glucose uptake and glycogen synthase activation [21,23,24,25,26,27], as well as altered insulin stimulation of PI 3-kinase activity [26,28]. These cell cultures are thus a relevant and interesting model to verify whether and how drug treatments could improve insulin action in human muscle cells.…”
Section: Introductionmentioning
confidence: 99%
“…3). This cell model displays several features of mature skeletal muscle, and myotubes derived from type 2 diabetic patients have consistently been shown to retain an insulin resistant phenotype with altered insulin-dependent glucose and lipid metabolism [29,30,36,37] and defective insulin signalling [20,36]. These defects include strong reduction in the activation of PI3K in response to insulin [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…The defect in activation of glycogen synthase is also present in normoglycemic subjects with a family history of diabetes (8). Moreover, the defect in insulin-stimulated glycogen synthase activity persists when skeletal muscle cells from type 2 diabetic patients are cultured under "normoglycemic" conditions (20); in that study, Jackson et al (20) reported that protein expression of insulin receptor substrate (IRS)-1, p85, Akt, and glycogen synthase was normal. However, the defect in insulin activation of glycogen synthase could have resulted from a proximal defect in the activity of the insulin receptor signal transduction system and not be intrinsic to glycogen synthase.…”
mentioning
confidence: 95%